Estimated global resources needed to attain universal coverage of maternal and newborn health services - Benjamin Johns; Kristjana Sigurbjörnsdóttir; Helga Fogstad; Jelka Zupan; Matthews Mathai; Tessa Tan-Torres Edejer (The World Health Organization, 2007)
OBJECTIVE: To estimate the amount of additional resources needed to scale up maternal and newborn health services within the context of the Millennium Development Goals, and to inform countries, donors and multilateral agencies about the resources needed to achieve these goals. METHODS: A costing model based on WHO's clinical guidelines was used to estimate the incremental resource needs for maternal and newborn health care in 75 countries. The model estimated the costs for care during pregnancy, childbirth, the neonatal period and the postpartum period, as well as the costs for postpartum family planning and counselling, abortion and post-abortion care; programme-level costs were also estimated. An ingredients-based approach, with financial costs for the years 2006 to 2015 as the output, allowed estimates to be made of country-specific and year-specific populations, unit costs and scale-up rates. Two scenarios using different scale-up rates were used (moderate and rapid). FINDINGS: The results show that a minimum yearly average increase in resources of US$ 3.9 billion is needed, although annual costs increase over the time period of the model. When more rapid rates of scale-up are assumed, this minimum figure may be as high as US$ 5.6 billion per year. The 10-year estimated incremental costs range from US$ 39.3 billion for a moderate scale-up scenario to US$ 55.7 billion for the rapid scale-up scenario. CONCLUSION: These projections of future financial costs may be used as a starting point for mobilizing global resources. Countries will have to further refine these estimates, but these figures may serve as goals towards which donors can direct their plans. Further research is needed to measure the costs of health system reforms, such as recruiting, training and retaining a sufficient number of personnel.